2023
DOI: 10.1108/nfs-09-2022-0338
|View full text |Cite
|
Sign up to set email alerts
|

Association between diet quality and BMI with side effects of Pfizer-BioNTech COVID-19 vaccine and SARS-CoV-2 immunoglobulin G titers

Abstract: Purpose The nutritional and anthropometric status can be essential in determining their immune response to vaccines. The purpose of this paper was to investigate the association between diet quality and anthropometric indices with the side effects of the Pfizer-BioNTech COVID-19 vaccine and the SARS-CoV-2 immunoglobulin G titer among Kurdish adults. Design/methodology/approach This cross-sectional survey-based study was conducted between December 2021 and February 2022. This paper included data on 115 adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…In addition, contrary to our ndings, the male gender had lower IgG levels after vaccination [38]. It has been reported that people with a healthy diet habits showed greater IgG titers following the rst and second doses of the COVID-19 vaccine than those with less healthy eating habits [39].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, contrary to our ndings, the male gender had lower IgG levels after vaccination [38]. It has been reported that people with a healthy diet habits showed greater IgG titers following the rst and second doses of the COVID-19 vaccine than those with less healthy eating habits [39].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, contrary to our findings, the male gender had lower IgG levels after vaccination [ 37 ]. It has been reported that people with healthy dietary habits showed greater IgG titers following the first and second doses of the COVID-19 vaccine than those with less healthy eating habits [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring SARS‐CoV‐2 mutations and their respective frequencies is an essential backup for the discovery of drug of choice and vaccines industry 27 . Presumably, world well‐known organizations somehow can gain benefit from the output of this kind of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…26 Monitoring SARS-CoV-2 mutations and their respective frequencies is an essential backup for the discovery of drug of choice and vaccines industry. 27 Presumably, world well-known organizations somehow can gain benefit from the output of this kind of investigation. Consequently, prestigious and stepwise cooperation and collaboration with regard to genomics data of the epidemic is unavoidable to tackle this issue, which is facing humanity.…”
Section: Introductionmentioning
confidence: 99%